2014
DOI: 10.1080/09588221.2014.963123
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a computer-assisted pronunciation training (CAPT) technique for efficient classroom instruction

Abstract: This study investigates a computer-assisted pronunciation training (CAPT) technique that combines oral reading with peer review to improve pronunciation of Taiwanese English major students. In addition to traditional in-class instruction, students were given a short passage every week along with a recording of the respective text, read by a native speaker. They practiced at home by listening to the recordings, reading out loud while listening, recording themselves, and comparing their recordings to the native … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…These findings suggest that L2 students training with ASR‐based CAPT learn more efficiently than those studying through more traditional means. Similar results were found in a recent study by Luo (). Her findings showed that a combination of peer review and CAPT led to greater overall improvements in L2 English pronunciation than a control group.…”
Section: Introductionsupporting
confidence: 93%
“…These findings suggest that L2 students training with ASR‐based CAPT learn more efficiently than those studying through more traditional means. Similar results were found in a recent study by Luo (). Her findings showed that a combination of peer review and CAPT led to greater overall improvements in L2 English pronunciation than a control group.…”
Section: Introductionsupporting
confidence: 93%
“…Learners' concerns, therefore, seem to be convincing from a scholarly-driven point of view, but may be rather unwillingly taken up by teachers who generally prefer teaching materials that are internationally-designed by native speaking developers (see, for example, Zacharias, 2005). Learners in this study also call for the integration of other teaching aids such as technological tools that were found to provide invaluable assistance to teachers and learners in developing language fluency, particularly pronunciation (see, for example, AbuSeileek, 2007;Elimat & AbuSeileek, 2014;Luo, 2014;Neri, Mich, Gerosa, & Giuliani, 2008). In the light of such learner perspectives regarding the teaching materials, future efforts of educators and teachers in this study context are to be directed towards relooking at institutional policies and mandates regarding the choice of teaching materials and considering such learner views when deciding on, exploiting, or introducing teaching materials for pronunciation instruction.…”
Section: Discussionmentioning
confidence: 97%
“…Given its focus on instructor speech, the current study did not investigate student output; however, classroom observation notes indicated that pronunciation was discussed and corrective feedback was offered during individual and small group activities as well as during breaks. Future investigations would thus be strengthened by gathering data on these types of interactions (see, e.g., Luo, ).…”
Section: Discussionmentioning
confidence: 99%